Synthesis and biological activity of fluorinated 7-benzylamino-2-phenyl-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amines - Dolzhenko, Anton; Tan, B.; Chiu, G.; Chui, W.; Dolzhenko, A. (Elsevier, 2015)
New fluorinated 7-benzylamino-2-phenyl-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amines were designed as potential anticancer agents and a practical method for their preparation was developed. The reaction of benzhydrazide with cyanoguanidine followed by intramolecular cyclocondensation resulted in the formation of triazolylguanidine, which upon condensation with trichloroacetonitrile afforded a key intermediate - 2-phenyl-7-trichloromethyl-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amine. In mild conditions, this intermediate underwent nucleophilic displacement of the trichloromethyl group with a series of fluorinated benzylamines providing the target compounds. Antiproliferative activity of the prepared compounds against the lung and breast cancer cells was explored. Together with anticancer effect, some compounds demonstrated anti-angiogenic properties.